Transparencia en la información de las empresas que cotizan en la bolsa de valores de Quito y su incidencia en la responsabilidad social corporativa - Velásquez Amaya, Argenis Benjamín (2019)
The current degree work evaluates the quality of the information disclosed by the companies that are listed on the Stock Exchange in Quito (BVQ) through its web pages and as it affects Corporate Social Responsibility (CSR). For the development of this research, the three-phase ordering with its respective activities was established, said execution, consists in the identification of significant indicators that allow the evaluation of the information disclosed in the web pages by the listed companies in favor of the public interest; the bibliographic inquiry allowed to know indicators or areas of transparency that have been used by different control agencies, through the accessible use of information for the stakeholders groups in order to maintain good CSR practices, four areas were established with their respective oriented subindicators To the private sector, once the evaluation instrument was established, the websites of the 153 companies selected in the sample were explored. The dichotomous variable was applied as a qualification method depending on the presence or absence of information according to the indicator, when obtaining the qualification, the information was summarized in an Excel sheet to enter the data into the STATA statistical program to determine the descriptive statistics, its level of significance and correlation. Therefore, the level of transparency of the companies listed on the BVQ was known. To conclude, the incidence of information against CSR was determined.